2021
DOI: 10.21082/bulpa.v19n1.2021.p41-63
|View full text |Cite
|
Sign up to set email alerts
|

Beauveria bassiana: Biopestisida Ramah Lingkungan dan Efektif untuk Mengendalikan Hama dan Penyakit Tanaman

Abstract: Beauveria bassiana merupakan salah satu jenis cendawan entomopatogen yang termasuk dalam divisi Ascomycota, kelas Sordariomycetes, ordo Hypocreales dan famili Clavicipitaceae. B. bassiana dapat membunuh seluruh stadia serangga pada berbagai jenis hama tanaman dari ordo Homoptera, Hemiptera, Coleoptera, Lepidoptera, Orthoptera, Isoptera, Diptera, dan Hymenoptera. Efikasi B. bassiana dipengaruhi oleh berbagai jenis enzim yang dihasilkan yaitu: kitinase, protease, amilase, dan lipase yang berfungsi sebagai pendeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 65 publications
(72 reference statements)
0
7
0
4
Order By: Relevance
“…Furthermore, [22] confirmed that the biopesticidal efficacy of the entomopathogenic fungus B. bassiana combined with plastic mulch to cover bunds was very significant in suppressing tuber damage by up to 99% of attacks by C. formicarius larvae. The results of a study conducted by [23] indicated that the efficacy of B. bassiana biopesticides applied to suppress tuber damage due to borer attack could be seen from the number of insect deaths, the number of eggs that did not hatched, and the weight of tubers that were suitable for consumption [24]. Meanwhile, according to [25], to increase and maintain the efficacy of the entomopathogenic fungus B. bassiana in killing target insects, the fungus must have an abundance of chitinase enzymes.…”
Section: Level Of Tuber Damagementioning
confidence: 99%
“…Furthermore, [22] confirmed that the biopesticidal efficacy of the entomopathogenic fungus B. bassiana combined with plastic mulch to cover bunds was very significant in suppressing tuber damage by up to 99% of attacks by C. formicarius larvae. The results of a study conducted by [23] indicated that the efficacy of B. bassiana biopesticides applied to suppress tuber damage due to borer attack could be seen from the number of insect deaths, the number of eggs that did not hatched, and the weight of tubers that were suitable for consumption [24]. Meanwhile, according to [25], to increase and maintain the efficacy of the entomopathogenic fungus B. bassiana in killing target insects, the fungus must have an abundance of chitinase enzymes.…”
Section: Level Of Tuber Damagementioning
confidence: 99%
“…The presence of fungal mycelia covering the insect's body can be noticed in insects that die after becoming infected with entomopathogenic fungus. Each genus of entomopathogenic fungi has a unique mycelium shape and color, such as the white mycelia of the genus Beuveria (Permadi;Sari, 2018;Bayu;Indiati, 2021;Qayyum et al, 2021), the green or greenish yellow mycelia of the genus Metharizium (Sanjaya;Ocampo;Caoili, 2013). The first signs of entomopathogenic fungus infection in insects include weakness and decreased feeding activity, which leads to eventual death (Pertiwi et al, 2016;Altinok;Altinok;Koca, 2019;Kova;Lackovi;Pernek, 2020).…”
Section: Entomopathogenic Fungal Attack Rate On Cbbmentioning
confidence: 99%
“…The first signs of entomopathogenic fungus infection in insects include weakness and decreased feeding activity, which leads to eventual death (Pertiwi et al, 2016;Altinok;Altinok;Koca, 2019;Kova;Lackovi;Pernek, 2020). Insects that die from being afflicted with fungi become hardened like mummies (Pertiwi et al, 2016;Bayu;Indiati, 2021).…”
Section: Entomopathogenic Fungal Attack Rate On Cbbmentioning
confidence: 99%
“…B. bassiana is a biological control agent for the class of entomopathogenic fungi which can kill various species and stages of insects starting from the egg, nymph/larva, and adult phases. The effectiveness of B. bassiana is related to the production of enzymes, and toxins that affect the nervous system and kill the host insect, so it has high potential to be used as a biological active ingredient to control pests [7]. B. bassiana produces various decomposing enzymes to help spores and hyphae enter through the insect cuticle [8].…”
Section: Introductionmentioning
confidence: 99%